Muscles and the Media: A Natural Experiment Across Cultures in Men’s Body Image - Thornborrow, Tracey; Onwuegbusi, Tochukwu; Mohamed, Sophie; Boothroyd, Lynda G.; Tovée, Martin J. (Frontiers in Psychology, 2020)
An increasing number of studies are evidencing relationships between the drive for muscularity and potentially harmful behavioural strategies, such as unhealthy dieting and steroid use amongst men in WEIRD (Western, Educated, Industrialised, Rich, Democratic) populations. As such Western appearance standards proliferate around the world via the media, men who live in other cultural contexts are also at risk of potentially negative effects from aspiring to the ‘muscular ideal’. However, few studies have explored these relationships in non-WEIRD populations. We investigated men’s body ideals and body image in two non-WEIRD, non-White populations, Uganda (Africa) and Nicaragua (Central America), and compared them with an ethnically diverse sample of U.K men. We also examined whether socio-cultural factors including media and ethnicity, predicted the drive for muscularity and body change behaviours among our participants. Results showed that Ugandan men had the least desire for muscularity relative to UK men. Supporting the Tripartite model we found that media and peer influences significantly predicted the drive for muscularity, particularly among men from White British and Nicaraguan Miskitu ethnic groups. By contrast, Creole and Mestizo men from Nicaragua were more likely to want to increase muscularity relative to Black African men from Uganda. Overall, our findings support previous research in demonstrating that there are cultural differences in the kind of body men desire, and that men from WEIRD and non-WEIRD populations may experience similar pressures to aspire to and attain a muscular body type.